Soft X‐ray angle‐resolved photoemission with micro‐positioning techniques for metallic V2O3. (13th April 2015) - Fujiwara, Hidenori; Kiss, Takayuki; Wakabayashi, Yuki K.; Nishitani, Yoshito; Mori, Takeo; Nakata, Yuki; Kitayama, Satoshi; Fukushima, Kazuaki; Ikeda, Shinji; Fuchimoto, Hiroto; Minowa, Yosuke; Mo, Sung‐Kwan; et al.
<x xml:space="preserve">Abstract</x> Soft X‐ray angle‐resolved photoemission has been performed for metallic V2O3. By combining a microfocus beam (40 µm × 65 µm) and micro‐positioning techniques with a long‐working‐distance microscope, it has been possible to observe band dispersions from tiny cleavage surfaces with a typical size of several tens of µm. The photoemission spectra show a clear position dependence, reflecting the morphology of the cleaved sample surface. By selecting high‐quality flat regions on the sample surface, it has been possible to perform band mapping using both photon‐energy and polar‐angle dependences, opening the door to three‐dimensional angle‐resolved photoemission spectroscopy for typical three‐dimensional correlated materials where large cleavage planes are rarely obtained.